Randomized, multicenter study: on-demand versus continuous maintenance treatment with esomeprazole in patients with non-erosive gastroesophageal reflux disease. Issue 1 (December 2016) - Bayerdörffer, Ekkehard; Bigard, Marc-Andre; Weiss, Werner; Mearin, Fermín; Rodrigo, Luis; Dominguez Muñoz, Juan; Grundling, Hennie; Persson, Tore; Svedberg, Lars-Erik; Keeling, Nanna; Eklund, Stefan
Abstract Background Most patients with gastroesophageal reflux disease experience symptomatic relapse after stopping acid-suppressive medication. The aim of this study was to compare willingness to continue treatment with esomeprazole on-demand versus continuous maintenance therapy for symptom control in patients with non-erosive reflux disease (NERD) after 6 months. Methods This multicenter, open-label, randomized, parallel-group study enrolled adults with NERD who were heartburn-free after 4 weeks' treatment with esomeprazole 20 mg daily. Patients received esomeprazole 20 mg daily continuously or on-demand for 6 months. The primary variable was discontinuation due to unsatisfactory treatment. On-demand treatment was considered non-inferior if the upper limit of the one-sided 95 % confidence interval (CI) for the difference between treatments was <10 %. Results Of 877 patients enrolled, 598 were randomized to maintenance treatment (continuous:n  = 297; on-demand:n  = 301). Discontinuation due to unsatisfactory treatment was 6.3 % for on-demand and 9.8 % for continuous treatment (difference −3.5 % [90 % CI: −7.1 %, 0.2 %]). In total, 82.1 and 86.2 % of patients taking on-demand and continuous therapy, respectively, were satisfied with the treatment of heartburn and regurgitation symptoms, a secondary variable (P  = NS). Mean study drug consumption was 0.41 and 0.91 tablets/day, respectively. Overall, 5 % of the on-demand group developed reflux esophagitis versus none in the continuous group (P  < 0.0001). The Gastrointestinal Symptom Rating Scale Reflux dimension was also improved for continuous versus on-demand treatment. Esomeprazole was well tolerated. Conclusions In terms of willingness to continue treatment, on-demand treatment with esomeprazole 20 mg was non-inferior to continuous maintenance treatment and reduced medication usage in patients with NERD who had achieved symptom control with initial esomeprazole treatment. Trial registration ClinicalTrials.gov identifier (NCT number):NCT02670642 ; Date of registration: December 2015.